2020
DOI: 10.7717/peerj.9026
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of locomotive syndrome among older individuals: a confirmatory factor analysis of the 25-question Geriatric Locomotive Function Scale

Abstract: Background The 25-question Geriatric Locomotive Function Scale (GLFS-25) is widely used in daily clinical practice in evaluating locomotive syndrome (LS). The questionnaire contains 25 questions aiming to describe 6 aspects, including body pain, movement-related difficulty, usual care, social activities, cognitive status, and daily activities. However, its potential underlying latent factor structure of the questionnaire has not been fully examined so far. Methods Five hundred participants who were 60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…The GLFS-25 is a self-administered questionnaire, consisting of 25 items graded on a 5-point scale, ranging from no impairment (0 points) to severe impairment (4 points). The sum of these scores is the total possible score, which ranges between 0 and 100; increasing values indicate increasing severity of LS [ 16 18 ]. This measurement has been validated as evaluating activities of daily life for the Japanese elderly population and for elderly people of other races.…”
Section: Methodsmentioning
confidence: 99%
“…The GLFS-25 is a self-administered questionnaire, consisting of 25 items graded on a 5-point scale, ranging from no impairment (0 points) to severe impairment (4 points). The sum of these scores is the total possible score, which ranges between 0 and 100; increasing values indicate increasing severity of LS [ 16 18 ]. This measurement has been validated as evaluating activities of daily life for the Japanese elderly population and for elderly people of other races.…”
Section: Methodsmentioning
confidence: 99%
“…While other studies only measure respondents with one gender only. In some of these studies there are also differences in measuring instruments, in which some studies use the lococheck measurement tool, while other studies use the GLFS-25 measuring instrument 14,15,16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…While there are studies in which cemented hemiarthroplasty was performed and patients were mobilized early [25], some other studies regarding uncemented hemiarthroplasty have also been conducted [26]. Wang et al [27] published a research about the need to load weight on the operated extremity for independent mobilization, due to atrophy and arthrosis in the upper extremities of geriatric patients. In our study, in accordance with the literature, it was observed that patients who underwent LFS-PBH were mobilized earlier than those in the PFN group.…”
Section: Discussionmentioning
confidence: 99%